Risks of Adverse Events Following Coprescription of Statins and Calcium Channel Blockers: A Nationwide Population-Based Study. Issue 2 (January 2016) - Wang, Yi-Chun; Hsieh, Tsung-Cheng; Chou, Chu-Lin; Wu, Jung-Lun; Fang, Te-Chao
Abstract : Abstract: Some statins (simvastatin, lovastatin, and atorvastatin) are metabolized by cytochrome P450s 3A4 (CYP3A4). Inhibitors of CYP3A4 including some calcium channel blockers (CCBs) might increase statin blood concentration, owing to drug–drug interactions. Risk of adverse events such as acute kidney injury might occur following the coprescription of CYP3A4-metabolized statins and CCBs that inhibit CYP3A4. This was a population-based cohort study. The study analyzed data of patients treated between 1997 and 2011, retrieved from Taiwan's National Health Insurance database. We enrolled 32, 801 patients who received coprescription of statins and CCBs that inhibit CYP3A4 (amlodipine, diltiazem, felodipine nicardipine, nifedipine, and verapamil). These patients were divided into 2 groups, according to whether they had received CYP3A4-metabolized statins (lovastatin, simvastatin, and atorvastatin) or non-CYP3A4-metabolized statins (fluvastatin, rosuvastatin, and pitavastatin). These 2 groups were 1:1 matched by age, gender, and Carlson comorbidity index. All outcomes were assessed within 90 days following drug coprescription. In this study, 5857 patients received coprescription of CYP3A4-metabolized statins and CCBs that inhibit CYP3A4. There were no differences in comorbidity or use of antihypertensive drugs between patients who received CYP3A4-metabolized statins and those who received non-CYP3A4-metabolized statins. Patients who received CYP3A4-metabolized statins had significantly higher risk of acute kidney injury (adjusted odds ratio [OR] = 2.12; 95% CI = 1.35–3.35), hyperkalemia (adjusted OR = 2.94; 95% CI = 1.36–6.35), acute myocardial infarction (adjusted OR = 1.55; 95% CI = 1.16–2.07), and acute ischemic stroke (adjusted OR = 1.35; 95% CI = 1.08–1.68) than those who received non-CYP3A4-metabolized statins. This nationwide cohort study demonstrated the increased risk of adverse events following the coprescription of CYP3A4-metabolized statins and CCBs that inhibit CYP3A4. Therefore, it is important to take into account the potential adverse events while coprescribing CYP3A4-metabolized statins and CCBs that inhibit CYP3A4.